2023
DOI: 10.1111/all.15747
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab improves long‐term outcomes in patients with uncontrolled, moderate‐to‐severe GINA‐based type 2 asthma, irrespective of allergic status

Abstract: Background: Previous research has shown greater efficacy of dupilumab in patients with uncontrolled asthma and type 2 inflammation. We analyzed dupilumab's efficacy in patients from the TRAVERSE study with or without evidence of allergic asthma and type 2 inflammation per current GINA guidelines (≥150 eosinophils/μL or FeNO ≥20 ppb).Methods: All patients aged ≥12 years who rolled over from the placebo-controlled QUEST study (NCT02414854) to TRAVERSE (NCT02134028) received add-on dupilumab 300 mg every 2 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Another recent analysis of the SINUS population demonstrated dupilumab efficacy in patients with CRSwNP and coexisting asthma irrespective of the severity of their asthma at baseline, 13 while the TRAVERSE study demonstrated dupilumab efficacy in patients with Global Initiative for Asthma (GINA)-defined type 2 asthma and CRSwNP. 14 The efficacy of dupilumab in CRSwNP and asthma may be explained by its mechanism of action in targeting IL-4 and IL-13, which are key drivers of type 2 inflammation in both diseases, 5,6 with more than 95% of the overall SINUS population having type 2 inflammatory disease on the basis of a range of biomarkers and clinical measures. 15 Limitations of this analysis include its post hoc nature and the categorization of patients with asthma on the basis of selfreporting by the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent analysis of the SINUS population demonstrated dupilumab efficacy in patients with CRSwNP and coexisting asthma irrespective of the severity of their asthma at baseline, 13 while the TRAVERSE study demonstrated dupilumab efficacy in patients with Global Initiative for Asthma (GINA)-defined type 2 asthma and CRSwNP. 14 The efficacy of dupilumab in CRSwNP and asthma may be explained by its mechanism of action in targeting IL-4 and IL-13, which are key drivers of type 2 inflammation in both diseases, 5,6 with more than 95% of the overall SINUS population having type 2 inflammatory disease on the basis of a range of biomarkers and clinical measures. 15 Limitations of this analysis include its post hoc nature and the categorization of patients with asthma on the basis of selfreporting by the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high IgE at baseline in several diseases show clinical benefit with anti‐IL‐4Rα (dupilumab) treatment, for example, in alopecia areata, allergic asthma, and atopic dermatitis. 163 , 164 , 165 , 166 Dupilumab causes downmodulation and internalization of IL4Rα 167 to interfere with the IL‐4 signaling that is an absolute requirement for IgE CSR. 106 While dupilumab might affect additional aspects of atopic disease, 168 , 169 , 170 dupilumab leads to a 20%–50% drop in serum IgE over several months, 166 , 171 , 172 , 173 , 174 and >80% loss over treatment periods of 1 year or more 175 , 176 , 177 , 178 in allergic asthma, allergic rhinitis with or without nasal polyps, and atopic dermatitis patients, which fits with the notion that most IgE + ASC are short‐lived cells in these diseases.…”
Section: The Life Spans Of Ige + Ascmentioning
confidence: 99%